Trabajo, subjetividad y clínicas del trabajo : una aproximación al estado de su cuestión en el caso colombiano - Johnny Orejuela; María del Mar Pérez; Andrés Vásquez (Universidade do Porto, 2019)
The purpose of this document is to present an update on work clinics research in the Colombian academic context. The value of this state-of-the-art research is that it offers the possibility of representing ourselves and placing on the academic map an alternative perspective of the psychology of occupational health. Three relevant aspects will be discussed to fulfill this task. First, to make an initial approach to the conditions that characterize clinics as a clinical-critical approach to the work-subjectivity-occupational health relationship. Second, it is indicated as a predecessor context : research on the work-subjectivity relationship in Colombia, which in our country has been generally approached by the multi‑field of work psychology and organizations. Finally, to describe the progressive emergence and institutionalization of work clinics in Colombia (publication, events, postgraduate studies, thesis, etc.) in some universities, mainly in the cities of Cali and Medellin.